Ultrastructure of myoepithelial cells as a target cell in sialoadenitis of submandibular glands of lupus-prone female NZBxNZWF1 mice - Hayashi, Toshiharu; Hayashi, Hideyuki; Fujii, Taeko; Adachi, Chie; Hasegawa, Keiko (Virchows Archiv : an international journal of pathology, 2008)
The changes of myoepithelial cells of sialoadenitis in submandibular glands in lupus-prone female NZB × NZWF 1 (B/WF 1 ) mice, a model for human secondary Sjögren’s syndrome (sSS), were examined ultrastructurally. Inflammatory foci consisting of mainly lymphoid cells (lymphocytes and plasma cells) in the interlobular interstitium began to develop from 18 weeks of ages, and those were found within acini from the age of 25 weeks. These were paralleled with the production of anti-double-stranded deoxyribonucleic acid and anti-Ro/SS-A antibodies with age. Infiltrated lymphoid cells consisted of CD4 + T cells and Ig + (or IgG2a + ) cells. Electron microscopy revealed destruction of myoepithelial cells with lysis of basement membranes contacted with either lymphocytes or plasma cells. These led to the destruction (degeneration and necrosis) of the epithelium in striated and intercalated ducts and acinar epithelium. Further destruction of those cells occurred by the invasion of lymphocytes into the epithelial layers. Small numbers of apoptotic myoepithelium and duct epithelium from the age of 25 to 36 weeks and an increase of those cells in survived mice at 44 weeks of age were observed. The present study suggests that the myoepithelium may be one of the target cells and that the destruction of myoepithelial cells by infiltrated lymphoid cells may precede the destruction of acinar ducts and epithelium in sialoadenitis in sSS.